Epidemiology of RHDV2 (Lagovirus europaeus/GI.2) in free‐living wild European rabbits in Portugal. Issue 2 (17th November 2017) - Rouco, C.; Abrantes, J.; Serronha, A.; Lopes, A. M.; Maio, E.; Magalhães, M. J.; Blanco, E.; Bárcena, J.; Esteves, P. J.; Santos, N.; Alves, P. C.; Monterroso, P.
Summary: As the detection of the first outbreak of a novel aetiological agent of rabbit haemorrhagic disease commonly called RHDV2 or RHDVb ( Lagovirus europaeus /GI.2, henceforth GI.2) in France in 2010, the virus rapidly spread throughout continental Europe and nearby islands such as Great Britain, Sardinia, Sicily, the Azores and the Canary Islands among others. The outbreaks of this new lagovirus cause important economic losses in rabbitries, and ecological disruptions by affecting the conservation of rabbit‐sensitive top predators. We analysed 550 rabbit carcasses collected in the field between May 2013 and March 2016, to investigate the epidemiology of GI.2 in free‐living populations and to perform a comparative analysis with the epidemiology of classical rabbit haemorrhagic disease virus forms (RHDV, henceforth GI.1) in Portugal. Rabbits were sexed, aged and liver and blood samples were collected for subsequent RHDV screening and serology. A total of 172 samples were PCR‐positive to GI.2, whereas GI.1 strains were not detected in any of the samples. The outbreaks of GI.2 revealed a marked seasonality, with peaks during the breeding season (November‐May). We also found that approximately, one‐third of free‐ranging European rabbits in Portugal have seroconverted to GI.2. We demonstrate that the GI.2 lagovirus is currently widespread in wild populations in Portugal and is affecting a high proportion of adults and juveniles. Therefore, ongoing monitoring and surveillance are required to assess the effects of GI.2 on wild rabbit populations, its evolution, and to guide management actions aimed at mitigating the impacts of rabbit declines in the ecosystem and in rural economies.